Advanced Bifunctional Oxygen Reduction and Evolution Electrocatalyst Derived from Surface‐Mounted Metal–Organic Frameworks. (29th January 2020) - Li, Weijin; Xue, Song; Watzele, Sebastian; Hou, Shujin; Fichtner, Johannes; Semrau, A. Lisa; Zhou, Liujiang; Welle, Alexander; Bandarenka, Aliaksandr S.; Fischer, Roland A.
Abstract: Metal–organic frameworks (MOFs) and their derivatives are considered as promising catalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), which are important for many energy provision technologies, such as electrolyzers, fuel cells and some types of advanced batteries. In this work, a "strain modulation" approach has been applied through the use of surface‐mounted NiFe‐MOFs in order to design an advanced bifunctional ORR/OER electrocatalyst. The material exhibits an excellent OER activity in alkaline media, reaching an industrially relevant current density of 200 mA cm −2 at an overpotential of only ≈210 mV. It demonstrates operational long‐term stability even at a high current density of 500 mA cm −2 and exhibits the so far narrowest "overpotential window" Δ E ORR‐OER of 0.69 V in 0.1 m KOH with a mass loading being two orders of magnitude lower than that of benchmark electrocatalysts. Abstract : Eine Dehnungsstrategie wurde genutzt, um einen NiFe‐basierten ORR/OER‐Elektrokatalysator herzustellen, der von oberflächengebundene metallorganischen Gerüsten durch gezielte Einführung von funktionellen Gruppen in den organischen Linker abgeleitet ist. Der Katalysator zeigt eine hohe OER‐Aktivität und erreicht industriell relevante Stromdichten. Als bifunktioneller Katalysator zeigt er ein enges Überpotentialfenster von ≈0.69 V in 0.1 M KOH, was bisher beschriebene Systeme übertrifft.